Manejo de plasma rico en plaquetas (PRP) en el tratamiento de endometritis subclínica equina (2021)
Endometritis is an internal inflammation of the uterus, in which there are different processes and enzymes that are intended to defend against external agents that attack the internal wall of this organ and that finally triggers the signs and symptoms of the pathology, this has a prevalence of 30% within the infectious and inflammatory processes that cause infertility in equine species, the high rate of appearance is due in certain cases to an inadequate treatment resulting in bacterial resistance, but also to an inopportune diagnosis, therefore an effective clinical examination, sampling and diagnostic imaging to assess the type of endometritis and the condition of the uterus. Having an accurate diagnosis, a treatment can be chosen, which in these cases is the use of Platelet Rich Plasma (PRP), which is a volume of plasma with a platelet count, which contain numerous proteins, cytokines and various factors. Of growth, which help to repair the injured tissue, being an optimal solution in the treatment and that the results in the recovery are almost immediate, it is low cost and easy to use.